Biology and feeding habits of Delphastus pusillus (Coleoptera: Coccinellidae) predator of whiteflies - GARCÍA-GONZÁLEZ, JAVIER; LÓPEZ-AVILA, A. (Revista Colombiana de Entomología, 1998)
Delphastus pusillus (Le Come) has been registered as a voracious predator of immature stages of some species of whitefly mainly on Trialeurodes vaporo riorum and Bemisia tabaci in different crops and agricultura] regions of Colombia. This research was carried out to determine some aspects of the life history, feeding behavior, and basic rearing requirements of D. pusillus in order to establish a greenhouse colony and provide a preliminary assessment of its potential as biological control of whiteflies. The insect colony was maintained in a rearing room at 25 ± 2 °C and 58 ± 5% relative humidity, and in a greenhouse on T vaporariorum. Having established the insect colony in the laboratory the life cycle study was began making observations of its stages. duration, dimensions, habas, and behavior. To determine the compsumption capacity of larval third instar and adult predator, a bioassay was performed evaluating the number of consumed individuals by a predator as eggs, 1, II, and IV instar nymphs of the greenhouse whitefly in 24 hours. The insect undergoes four different stages on its development: egg, larva with four larval instars, pupa, and imago, completing its life cycle in 29.2 days average. The average time of each stage was: egg 6.8 days, 1 larval ínstar 3.6 days, II larval instar 2.1 days. III larval instar 2.7 days. IV larval instar 6.8 days and pupa 7.3 days. With regard of predator for consumption capacity. adult state and third larval instar had a major feeding by first instar nymphs of the greenhouse whitefly against the lower consumption were in fourth instar nymphs.